IFRS – 10 years later. Issue 5 (28th July 2016) - Ball, Ray
Abstract : A decade ago, the near-simultaneous adoption of International Financial Reporting Standards (IFRS) in over 100 countries could fairly have been described as a brave new world in financial reporting. Any systems innovation, and especially an innovation of such importance and magnitude, thrusts those involved (companies, users, and accountants) into the unknown. There was good reason to expect success, based largely on widespread enthusiasm for international standards and, behind that, recognition of the strong forces of globalization. Nevertheless, there were risks involved and there was limited a priori evidence to guide the decision-makers. A decade later, this is still the case. Globalization remains a potent economic and political force, and drives the demand for globalization in accounting. Nevertheless, most political and commercial activity remains local, so adoption of uniform rules does not by itself lead to uniform reporting behavior around the world. For many of the claimed benefits of IFRS adoption to be realized, uniform implementation would have to occur in a wide range of countries, which seems unlikely and requires more than simply creating regulatory enforcement mechanisms. Some evidence of actual outcomes from IFRS adoption has come to light, but, as will be argued below, by and large the evidence to date is not very useful. The IASB's (International Accounting Standards Board) valuation-centric Conceptual Framework leads it to pay little or no heed to the use of accounting information in contracting, despite the lip service recent amendments pay to even the narrower notion of stewardship. So IFRS adoption is an innovation of historical proportions whose worldwide effects remain somewhat uncertain. The essay concludes with comments on the status of China and the US.